2013
DOI: 10.1517/17425255.2013.769521
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic evaluation and clinical utility of azilsartan medoxomil for the treatment of hypertension

Abstract: Clinical trials have demonstrated that azilsartan is superior to other angiotensin-receptor blockers in lowering blood pressure. However, the clinical blood pressure trials of azilsartan published to date have been mainly conducted in patients without serious comorbidities and it is not clear if azilsartan has advantages over other angiotensin-receptor blockers in the treatment of these types of hypertensive patients. In addition, it remains to be determined whether the specific pharmacologic and pharmacokinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…In our preliminary study, we observed that AZL-M concentration rose sharply 0.5 hours after administration and disappeared after 24 hours in both the normal and CSQ-tg mice (data not shown), in contrast to long-lasting pharmacokinetics in humans (Angeli et al, 2013). Also, 3-day-administration in CSQ-tg mice might be too short to achieve steady anti-hypertensive effect.…”
Section: Discussionmentioning
confidence: 84%
“…In our preliminary study, we observed that AZL-M concentration rose sharply 0.5 hours after administration and disappeared after 24 hours in both the normal and CSQ-tg mice (data not shown), in contrast to long-lasting pharmacokinetics in humans (Angeli et al, 2013). Also, 3-day-administration in CSQ-tg mice might be too short to achieve steady anti-hypertensive effect.…”
Section: Discussionmentioning
confidence: 84%
“…Beside antihypertensive drugs such as thiazide diuretics, β‐adrenoceptor antagonists (BAA) and calcium channel blockers, which have an effect on blood volume, heart rate and vasodilation, respectively , an important therapeutic approach for hypertension is the blockade of the renin–angiotensin–aldosterone system (RAAS). Azilsartan (AZL) was recently introduced for treatment of hypertension mainly due to unprecedented tight binding to the angiotensin receptor, AT 1 , and the pharmacokinetic and testing in animal studies as well as a proposed role in the human clinic have recently been reviewed . Here, we have focused on the strong interaction of the drug with the AT 1 receptor and whether that is reflected in the clinical effects of the drug and compared with other angiotensin receptor antagonists.…”
mentioning
confidence: 99%
“…Angiotensin II receptor blockers (ARBs) are a drug class generally considered to be among the best tolerated and more effective agents in the realm of antihypertensives, even though there are some differences between individual drugs . The eighth and the most recently approved drug of the ARBs is azilsartan medoxomil (AZL‐M); it is approved at doses of 20 to 80 mg once daily (40 to 80 mg in the United States), alone or in combination with other antihypertensive agents …”
mentioning
confidence: 99%
“…[5][6][7][8][9][10] The eighth and the most recently approved drug of the ARBs is azilsartan medoxomil (AZL-M); it is approved at doses of 20 to 80 mg once daily (40 to 80 mg in the United States), alone or in combination with other antihypertensive agents. [11][12][13][14][15][16][17] AZL-M is a prodrug potassium salt that is rapidly hydrolyzed to the active moiety, AZL, and is not detected in plasma after oral administration. After oral administration of AZL-M, peak plasma concentrations of AZL are reached within 1.5 to 3 hours.…”
mentioning
confidence: 99%